Combination of traditional Chinese bone setting and NMES technique for treating lumbar disc herniation: a case report - Bao, Yimei; Wang, ZhiJin (Frontiers in Rehabilitation Sciences, 2024)
ObjectiveTo analyze and study the causes and treatment approaches for lumbar disc herniation, focusing on office workers.MethodsThe concept of spinal internal balance disorder as a foundation for treating traumatic spinal diseases was introduced. Pathological changes occurring with single (or multiple) vertebral displacement were considered. For the first time, the “spinal (point) rotation repositioning method” from traditional Chinese bone setting was combined with NMES (neuromuscular electrical stimulation) technology to treat low back pain.ResultsThe patient's symptoms of low back pain were cured within a short period, allowing a quick return to work and daily life, with no recurrence of the disease observed during long-term follow-up.ConclusionThe combination of traditional Chinese bone setting and NMES provides a more effective and quicker resolution to low back pain in office workers with lumbar disc herniation. This integrated approach not only relieves pain but also restores lumbar function, ensuring long-term stability and reducing recurrence.